2011
DOI: 10.1073/pnas.1014660108
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase G9a is required for de novo DNA methylation and the establishment, but not the maintenance, of proviral silencing

Abstract: Methylation on lysine 9 of histone H3 (H3K9me) and DNA methylation play important roles in the transcriptional silencing of specific genes and repetitive elements. Both marks are detected on class I and II endogenous retroviruses (ERVs) in murine embryonic stem cells (mESCs). Recently, we reported that the H3K9-specific lysine methyltransferase (KMTase) Eset/Setdb1/KMT1E is required for H3K9me3 and the maintenance of silencing of ERVs in mESCs. In contrast, G9a/Ehmt2/KMT1C is dispensable, despite the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 52 publications
4
93
0
Order By: Relevance
“…However, the alternate possibility of gene silencing resulting in spreading of H3K9me2 in a subset of the spreading domains cannot be ruled out. Nevertheless, H3K9me2 spreading into active regions remains a significant event because this could play a role in stably silencing the genes, given that H3K9me2 could be a precursor to DNA methylation and long-term gene silencing (40,41). Although spreading of H3K9me2 into promoters was associated with reduction in gene expression, we detected a subset of genes whose expression was not affected by H3K9me2 spreading.…”
Section: Discussionmentioning
confidence: 64%
“…However, the alternate possibility of gene silencing resulting in spreading of H3K9me2 in a subset of the spreading domains cannot be ruled out. Nevertheless, H3K9me2 spreading into active regions remains a significant event because this could play a role in stably silencing the genes, given that H3K9me2 could be a precursor to DNA methylation and long-term gene silencing (40,41). Although spreading of H3K9me2 into promoters was associated with reduction in gene expression, we detected a subset of genes whose expression was not affected by H3K9me2 spreading.…”
Section: Discussionmentioning
confidence: 64%
“…Unmodified H3 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] peptide (23 μM) was incubated with 25 nM G9a-SET in the presence of 50 μM SAM (radioactive: nonradioactive molar ratio = 0.016) in a buffer containing 50 mM Hepes (pH 7.9), 0.5 mM DTT, 0.25 mM PMSF, and 2 mM MgCl 2 . Where applicable, different H3 1-20 K9X peptides (Tufts University Peptide Synthesis Core) were present in the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…G9a is an ∼120-kDa protein and contains an SET domain at its C terminus that catalyzes monoand dimethylation of histones at lysine 9 (11), and we previously showed that H3K9M peptides are capable of inhibiting activity of SUV39H1 and G9a, two H3K9-directed methyltransferases, in vitro (7). Recent studies identified a role for G9a in heterochromatin maintenance and transcriptional repression, such as the silencing of repeat elements, including long interspersed nuclear elements and endogenous retroviruses (12)(13)(14). Up-regulation of both G9a and G9a like protein (GLP) has implications in a variety of human cancers, including solid tumors as well as acute myeloid leukemia (15)(16)(17).…”
mentioning
confidence: 99%
“…Histone methylation is also crucial in thymocyte development, as reported in Trim28-deficient mice, which showed defective trimethylation of lysine 4 in histone 3 (5,6). In contrast to transcriptional activating epigenetic marks such as histone 3 lysine 4 methylation (7), the importance of repressive epigenetic marks such as histone 3 lysine 9 (H3K9) methylation (8) on T cell development is still obscure because deletion of Suv39h1, the first identified H3K9 histone methyltransferase (HMT), did not result in an apparent defect in thymocyte differentiation (9). Similarly, G9a, another methyltransferase regulating mono-and dimethylation of H3K9 (10,11), was also shown to be dispensable because G9a 2/2 mice had normal T cell differentiation (12).…”
mentioning
confidence: 99%